The moderating role of culture on the relationship between the country innovation and fintech industry development - Chiew, Xing Yi (Universiti Malaysia Sarawak (UNIMAS), 2019)
The aim of this research s to determine the moderating role of culture on the relationship between country innovation and the fintech industry development (FID). In this research, there are 41 sample countries which selected from the international forums. The sample period of this research is from the year of 2012 to the year of 2017, a total of 6 years. The estimation model is built by contesting two main theories, namely, the endogenous growth theory and the innovation culture theory. This study confirmed the effect of the country innovation and culture on the FID. Both the country innovation and culture illustrated a reverse relationship with FID. Moreover, there is a positive and significant effect on the relationship of country innovation and Fintech industry development.